Membangun Generasi Penggerak Wisata Digital Tosari, Bromo Tengger Semeru: Pelatihan Public Speaking dan Konten Kreatif - Zaman, Muhammad Badaruz; Asmoro Saputro, Rio; Maulana, Irfan (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Tosari Village, located in the Bromo Tengger Semeru National Park area, has great potential for nature and cultural tourism. However, this potential has not been exposed to its full extent due to a lack of digital promotion. On the other hand, the younger generation, especially students, do not yet have adequate skills to lead tourism promotion. This issue is resolved by a community service initiative that aims to increase the younger generation's capacity in Tosari Village. The purpose of this activity is to train students at Baithani Christian Middle and High School in Tosari in creative content creation and public speaking. The methods used include situation analysis, intensive training, direct practice, and mentoring. As a result, students showed significant improvements in their understanding and abilities, ranging from confidence in public speaking to mastery of basic promotional content creation techniques. Tosari Village's reputation as a top travel destination has been enhanced by this program's success in creating a new generation of people who are prepared to lead digital tourism as tourism ambasador.